A general esterolysis strategy for upcycling waste polyesters into high-value esters - Minghao Zhang; Yunkai Yu; Buxing Han; Qingqing Mei (Nature Communications)
Abstract The upcycling of waste polyesters into high-value chemicals offers a sustainable and economically viable solution to the global plastic waste crisis. Herein, we report a general esterolysis strategy for the efficient depolymerization of polyesters to produce high-value ester products, utilizing a broad range of esters, including carboxylates, carbonates, and C/Si/Ti/P-based esters. Using the 1-ethyl-3-methylimidazolium acetate as a highly effective catalyst, polyethylene terephthalate is selectively converted into dimethyl terephthalate and ethylene carbonate with remarkable yields of 99% and 90%, respectively. Mechanistic studies reveal that methanol, generated in situ via the 1-ethyl-3-methylimidazolium acetate-catalyzed hydrolysis of dimethyl carbonate, drives the cleavage of C–O ester bonds in polyethylene terephthalate. This strategy demonstrates broad applicability, achieving high conversion efficiencies across various mixed and colored commercial waste polyesters. The energy efficiency and versatility of this approach establish a transformative route to diverse high-value esters, advancing the development of circular plastic economies and sustainable chemistry.